Facile Access to Triazole-Fused 3,1-Benzoxazines Enabled by Metal-Free Base-Promoted Intramolecular C–O Coupling - Tatevosyan, Stepan S.; Kotovshchikov, Yury N.; Latyshev, Gennadij V.; Lukashev, Nikolay V.; Beletskaya, Irina P. (Synthesis, 2021)
A convenient approach to assemble 1,2,3-triazole-fused 4H-3,1-benzoxazines has been developed. Diverse alcohol-tethered 5-iodotriazoles, readily accessible by a modified protocol of Cu-catalyzed (3+2)-cycloaddition, were utilized as precursors of the target fused heterocycles. The intramolecular C–O coupling proceeded efficiently under base-mediated transition-metal-free conditions, furnishing cyclization products in yields up to 96%. Suppression of the competing reductive cleavage of the C–I bond was achieved by the use of Na2CO3 in acetonitrile at 100 °C. This practical and cost-effective procedure features a broad substrate scope and valuable functional group tolerance.
Keywords: triazoles; benzoxazines; heterocycles; fused-ring systems; C–O coupling; cycloaddition